Nordic Journal of African Studies, Vol 7 No 1 (1998) (Nordic Journal of African Studies, 1998)
• H. Weiss Relieving but not preventing – Public famine relief in some British colonies in Africa up to 1930• M. Vehnämäki Adjusted environment: Evidence from Ghana's structural adjustment program• A. M. Nangend The heartbeat and rhythm of life: The cardinal points in the socio-cultural construction of Bukisu personhood• P. Mikkola Random coincidence in mass comparison: Preliminary analysis of the Nilo-Saharan lexicon• O. Akinwumi The Abakwariga and the economic transformation of the Jukun, Kingdom of Wukari, ca. 1650–1900• J. A. Ògúnwá The derogation of masculinity in Yorùbá proverbs